2013
DOI: 10.5830/cvja-2013-069
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cultural, environmental and behavioural determinants of obesity in black South African women : review articles

Abstract: South Africa (SA) is undergoing a rapid epidemiological transition and has the highest prevalence of obesity in subSaharan Africa (SSA), with black women being the most affected (obesity prevalence 31.8%). Although genetic factors are important, socio-cultural, environmental and behavioural factors, as well as the influence of socio-economic status, more likely explain the high prevalence of obesity in black SA women. This review examines these determinants in black SA women, and compares them to their white c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
123
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 80 publications
8
123
1
2
Order By: Relevance
“…The sex-specific pattern of overweight and obesity reflects the general distribution reported across Africa [8,38] and in previous reports from Ghana [6,39,40]. The roles of endogenous and exogenous steroid exposure and biological differences in body fat distribution have been used to explain gender differences in overweight and obesity [16].…”
Section: Discussionmentioning
confidence: 59%
“…The sex-specific pattern of overweight and obesity reflects the general distribution reported across Africa [8,38] and in previous reports from Ghana [6,39,40]. The roles of endogenous and exogenous steroid exposure and biological differences in body fat distribution have been used to explain gender differences in overweight and obesity [16].…”
Section: Discussionmentioning
confidence: 59%
“…In a study on urban-dwelling black South Africans, it was suggested that the rapid rise in type 2 diabetes (T2D) prevalence is strongly related to higher adiposity levels, as more than 80% of the diabetic participants were either overweight or obese, and also had higher measures of abdominal adiposity compared to the non-diabetic participants [2,5]. The most recent national statistics on the prevalence of overweight and obesity in South Africa have reported that 64% of adult women and 30.7% of adult men are overweight or obese, with the numbers differing quite significantly between the ethnic groups [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Several sociocultural, environmental and behavioural determinants of obesity have been identified in black South African women [2,5]; however, it is uncertain if these factors predict BMI in black South African men. The sex difference in obesity prevalence in Africa [6,7] is not observed in high-income countries where obesity is more similar between the sexes [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Black South African women are supposed to have better access to health; however, they are still generally poorer and less educated, and have limited resources compared with the other ethnic groups in the country [2]. Rural-dwelling black South African women also have better activity profiles than urban-dwelling black women, resulting in lower disease risk [7]. With the continual shift of populations to the urban setting, beliefs around acceptable body size are being challenged; such that some obese black South African women perceive their body size to be too large.…”
Section: Introductionmentioning
confidence: 99%
“…With the continual shift of populations to the urban setting, beliefs around acceptable body size are being challenged; such that some obese black South African women perceive their body size to be too large. In the rural setting, being overweight is still associated with wealth and prosperity [7]. Even though these behavioural and psychosocial factors may pose potential challenges for lifestyle modification, they are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%